Faktor-Faktor Yang Mempengaruhi Kualitas Pelayanan Publik Di Puskesmas Bahu Kecamatan Malalayang Kota Madya Manado - Soputan, Jultje; Lengkong, Daicy; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : This research aims to know the factors that affect the quality of public services in Public Health Center Bahu, Malalayang Subdistrict Municipality of Manado, as well as to get an idea of the existing public services in Public Health Center Bahu, Malalayang Subdistrict municipality of manado. Public Health Center is spearheading the development of healthcare in the absence of successful neighborhood districts. Health development is an effort meet one of the basic rights of the people, namely people’s right to obtain access to healthcare needs. The main problem as a health service that many of its competitors is the service given is it appropriate or not public expectation therefore, Public Health Center Bahu, Malalayang Subdistrict municipality of manado is expected to always maintain the trust and satisfaction of the public by increasing the quality of service to the satisfaction of the patients improved. Public Health Center Bahu, Malalayang Sub district municipality of manado need to carefully determine the needs of patients in an effort to meet the expectations or desires and increase the satisfaction of services provided. The research methods used in this study is a qualitative method, with the techniques of primary and secondary data collection is done with the interview, observation and documentation study. As for the respondents/informants of this research is the head of the Public Health Center Bahu: 4 employees and health workers of Public Health Center: 5 community representatives 5 wards that constitute the coverage of the Public Health Center Bahu, among others, is the village’s Bahu, Kleak, Winangun I, Winagun II, and Batu Kota. The results showed that in view of the quality of public services for the Public Health Center Bahu is currently said to be the maximum. It happened because of the speed and timeliness in providing the service is still at a slow rate. From the above problems then in view of the factors that affect the quality of public services, such education, experience, compensation, and work environment, so many problems that arise from aspects of the four points above, with regard to the central issues that are encountered in terms of placement of employees who do not comply with the skills possessed by these employees, the lack of officers, while the work load is very much in compensation, received highly lacking and is not appropriate. In doing Ministry employee also in this still very less experience in taking care of the Administration and others, in addition to facilities and infrastructure in support of public service which is still very minimal, problem employee discipline and communication problems among fellow employees also should be on the increase. Referring to the discussion and the conclusions above, in order to improve the quality of recommend in public services in Public Health Center Bahu then recommend it â€“ it is as follows. The first need for the attention of the local authorities with regard to infrastructure work supporting employees, the need for additional employees at the clinics this shoulder, as well as the need for attention from the local Government regarding the compensation of employees and the health workforce in the value is still very small. Then the need for oversight of the performance of officers so that they can work properly and at maximum, while leaders must also be able to embrace all officers preparing a time to encourage and motivate each other between one another, so that in one instance appears mutual respect and had each other. Keywords: factors that affect the quality of public services